Creating New Ventures: A Review and Research Agenda - Shepherd, Dean A.; Souitaris, Vangelis; Gruber, Marc (Journal of management, 2021)
Creating new ventures is one of the most central topics to entrepreneurship and is a critical step from which many theories of management, organizational behavior, and strategic management build. Therefore, this review and proposed research agenda are relevant to not only entrepreneurship scholars but also other management scholars who wish to challenge some of the implicit assumptions of their current streams of research and extend the boundaries of their current theories to earlier in the organization’s life. Given that the last systematic review of the topic was published 16 years ago, and that the topic has evolved rapidly over this time, an overview and research outlook are long overdue. From our review, we inductively generated 10 subtopics: (a) lead founder, (b) founding team, (c) social relationships, (d) cognitions, (e) emergent organizing, (f) new-venture strategy, (g) organizational emergence, (h) new-venture legitimacy, (i) founder exit, and (j) entrepreneurial environment. These subtopics are then organized into three major stages of the entrepreneurial process: co-creating, organizing, and performing. Together, the framework provides a cohesive story of the past and a road map for future research on creating new ventures, focusing on the links connecting these subtopics.